Test–Retest Reliability of the Effects of Continuous Theta-Burst Stimulation - Jannati, Ali; Fried, Peter J.; Block, Gabrielle; Oberman, Lindsay M.; Rotenberg, Alexander; Pascual-Leone, Alvaro (Frontiers in Neuroscience, 2019)
Objectives: The utility of continuous theta-burst stimulation (cTBS) as index of cortical plasticity is limited by inadequate characterization of its test-retest reliability. Thus, we evaluated the reliability of cTBS aftereffects, and explored the roles of age, and brain-derived neurotrophic factor (BDNF) and apolipoprotein E (APOE) polymorphisms. Methods: 28 healthy adults (age range 21–65) underwent two identical cTBS sessions (median interval = 9.5 days) targeting the motor cortex. Intraclass correlation coefficients (ICCs) of the log-transformed, baseline-corrected amplitude of motor evoked potentials (ΔMEP) at 5–60 minutes post-cTBS (T5–T60) were calculated. Results: ΔMEP at T50 was the most-reliable cTBS measure in the whole sample (ICC = 0.53). Area under-the-curve (AUC) of ΔMEPs was most reliable when calculated over the full 60 minutes post-cTBS (ICC = 0.40). cTBS measures were substantially more reliable in younger participants (< 35 yr) and those with BDNF Val66Val and APOE ε4– genotypes. Conclusions: cTBS aftereffects are most reliable when assessed 50 minutes post-cTBS, or when cumulative ΔMEP measures are calculated over 30–60 minutes post-cTBS. Reliability of cTBS aftereffects is influenced by age, and BDNF and APOE polymorphisms. Reliability coefficients are used to adjust effect-size calculations for interpretation and planning of cTBS studies.